Pengaruh Disiplin Kerja, Kompetensi dan Stress Kerja terhadap Kinerja Karyawan pada PT. Subur Mekar Abadi - Melva Melany Sitompul; William Steven Wijaya; Feciliana Tangkas (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of work discipline, competence and work stress on employee performance at PT. Fertile Blooming Eternally. The phenomenon of declining employee performance is caused by a lack of employee discipline, poor competence and high work stress. The research method used is a quantitative approach. The type of research used is descriptive quantitative research and the nature of this research is explanatory research. Population is all employees of PT. Subur Mekar Abadi from January to December 2019 as many as 153 employees. The technique used in this research is simple random sampling technique. The number of samples in this study were 111 employees. For testing the Validity and Reliability Test, 30 employees were taken outside the research sample. The results showed that work discipline and work stress partially had a significant effect on employee performance, while competence partially had no significant effect on employee performance. Simultaneously work discipline, competence and work stress affect employee performance with a coefficient of determination of 34.5% and the remaining 65.5% is the influence of other independent variables not examined in this study such as financial compensation, etc.